The 2021 Western North American heat dome increased climate change anxiety among British Columbians: Results from a natural experiment - Andreea Bratu; Kiffer G. Card; Kalysha Closson; Niloufar Aran; Carly Marshall; Susan Clayton; Maya K. Gislason; Hasina Samji; Gina Martin; Melissa Lem; Carmen H. Logie; Tim K. Takaro; et al. (Elsevier, 2022)
Introduction: Extreme weather events caused by climate change pose a risk to mental health. Illustrating this reality, this study estimates the impact of the 2021 Western North American heat dome (June 25th, 2021 - July 1st, 2021) on climate change anxiety among British Columbians. Methods: We conducted an online survey of British Columbians, aged ≥ 16. Participants were recruited using paid advertisements on social media. Data were collected pre- and post- heat dome between May 12th, 2021 - June 21st, 2021 (n = 439), and July 15th, 2021 - July 18th, 2021 (n = 420), respectively. A multivariable inverse Gaussian regression model tested differences in Climate Change Anxiety Scale (CCAS) scores pre- and post- heat dome. Potential confounders measured included age, gender, ethnicity, education, income, and political orientation. CCAS reliability was assessed using Cronbach's alpha. Results: Most participants indicated that they were much (40.1%) or somewhat (18.4%) more worried about climate change due to the heat dome. Mean CCAS scores increased from 1.66 (standard deviation [SD]= 0.80) to 1.87 (SD = 0.87) pre- and post- heat dome, respectively. In multivariable modeling, this effect was significant after controlling for potential confounders (Estimate = 0.057, standard error = 0.148, p < 0.001). The CCAS reliability was high (Cronbach's alpha = 0.94). Discussion: Our results found that British Columbians had significantly higher climate change anxiety following the 2021 Western North American heat dome. Ongoing monitoring of climate change anxiety is needed to understand the impact of individual and compounding climate change-related weather events over time.